T1 Pelvic Angle Is a Useful Parameter for Postoperative Evaluation in Adult Spinal Deformity Patients. Issue 21 (1st November 2016) - Banno, Tomohiro; Hasegawa, Tomohiko; Yamato, Yu; Kobayashi, Sho; Togawa, Daisuke; Oe, Shin; Mihara, Yuki; Matsuyama, Yukihiro
Abstract : Study Design: Retrospective review. Objective: We investigated validity of T1 pelvic angle (TPA) for postoperative assessment and determined its target value for corrective scoliosis surgery. Summary of Background Data: TPA is a novel spinopelvic parameter accounting for both pelvic retroversion and trunk anteversion. As an angle, it is less affected by posture and correlates well with health-related quality of life in adult spinal deformity patients. According to our study in elderly volunteers, the threshold TPA value for disability (Oswestry Disability Index [ODI] score >20) was approximately 20°. Methods: Seventy adult scoliosis patients (5 men and 65 women; mean age, 67.8 yr) who underwent spinal deformity surgeries and were followed up for at least 2 years postoperatively were studied. The following parameters based on whole-spine and pelvic radiography were assessed preoperatively, soon after operation, and 2 years postoperatively: C7-central sacral vertical line, TPA, sagittal vertical axis (SVA), pelvic tilt, and pelvic incidence minus lumbar lordosis. ODI and Scoliosis Research Society-22 scores were obtained preoperatively and 2 years postoperatively. Based on postoperative TPA, patients were divided into two groups: ≤20° (group G) and greater than 20° (group P). Results: TPA and SVA correlated with health-related quality of life. Two years postoperatively, TPA best correlated with ODI and Scoliosis Research Society-22 scores, although all parameters correlated with them, and TPA soon after operation best correlated with ODI scores 2 years postoperatively. Two years postoperatively, each parameter and ODI scores in group G were better than those in group P. Conclusion: The correlation results showed that TPA appropriately assessed clinical outcomes following spinal deformity surgery. TPA assessed soon after operation correlated with ODI score 2 years postoperatively, and thus predicted prognosis. Because patients whose postoperative corrected TPA was 20° or lesser had better spinopelvic parameters and ODI scores 2 years postoperatively, TPA 20° or lesser was the proper target value for corrective surgery. Level of Evidence: 4